Review of Race, Politics, and Irish America: A Gothic History, by Mary M. Burke - Charlie Jorge (Review of Irish Studies in Europe, 2025)
Review of Race, Politics, and Irish America: A Gothic History, by Mary M. Burke (Oxford and New York: Oxford University Press, 2022), 272 pp., ISBN: 978–0–19–285973–0, £28.99 (hardback)